(3GdOQI GdeVjFI aj SjO Gdedhc hefGbH GdUGdMjfs
(3ChdgG (B:s
(3GdPi de jRd hdG jRGd CeG HYO aEfi deG fXQJ ai SjQ GdCee GdeGVjI heG hVYhg ef GdSjGSGJ ai JOHjQ GdOhd ahLOJ Pdc fhYjf CMcGe hSjGSGJ s
(3BNQgG (B:s
(3hbO bGd ajg GdChd dfG LdSGA eG fed MOjKge aEf bdJ CehGJ adSJ HcGPH agPG eG CQOfG fedjg ai gPG GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdSjGSI hGdGLJeGYs